The effectiveness of counseling based on Al-Fatihah psychology to reduce academic stress in students during the covid-19 pandemic - Ansyah, Eko Hardi; Paryontri, Ramon Ananda; Affandi, Ghozali Rusyid (University of Muhammadiyah Malang, 2023)
The study aims to determine whether counseling based on Al-Fatihah psychology can reduce student academic stress due to the covid-19 pandemic. This experimental pre-post design study comprises the experimental and control groups. The participants are 23 people selected using the purposive sampling method. The experimental group consisted of 11 people and was given treatment in counseling based on Al-Fatihah psychology for 4 weeks in 5 sessions. The academic stress scale was given to both groups as a pre-test before the treatment started in the experimental group. In contrast, the academic stress scale was given as a post-test after the last session. The data analysis's result using the Mann-Whitney U test on the gain score between the experimental and control groups showed a significant difference with p (0.022) <0.05. This indicates that counseling based on Al-Fatihah psychology effectively reduced students' academic stress levels during the pandemic.